The Teaching-Learning Process in Madrasah Multigrade Classes During the Pandemic: A Phenomenological Investigation - Salma Butig Redocto; Gideon Sindad Sumayo (AL-ISHLAH: Jurnal Pendidikan, 2024)
This qualitative study, employing a phenomenological approach, seeks to illuminate the experiences, challenges, and coping mechanisms of Madrasah multigrade teachers during the pandemic. The study involved 14 participants in in-depth interviews and 8 participants in a focus-group discussion. Thematic analysis was applied to analyze the responses. The research uncovered three fundamental themes in their lived experiences, focusing on establishing flexible teaching practices, adaptive instruction, and continuous assessment for enhanced learning. It also unveiled challenges at different levels, notably the three essential themes: Azatids-related challenges, Madrasah-level challenges, and Kalangkapan-level challenges. Despite these hurdles, the participants demonstrated their resilience through coping mechanisms, including spending own money, religious obligations, displaying positive attitude, praying, and self-reward. The study's conclusion underscores the profound impact of the COVID-19 pandemic on Madrasah multigrade teachers, emphasizing their ability to persist, adapt, and effectively cope with unprecedented changes.